FINANCIAL ATTITUDE DAN AKSES KREDIT FORMAL USAHA KECIL DI TAMAN SARI YOGYAKARTA - Diah Lestari Mumpuni; Pristin Prima Sari (Optimum: Jurnal Ekonomi dan Pembangunan, 2019)
Abstract This study aims to determine the level of financial attitudes increase the access of formal credit of Small Business Entreprise in Taman Sari Yogyakarta. This research uses questionnaire method to Small Business Owner in Taman Sari Yogyakarta. Data analysis techniques used are independent t test and regression analysis with SPSS 15th Edition. The result of the research is levene test and t value on Independent test test showed that positive significant value (levene test significance value is 0,023, F value is 5,479 and t value is 2,33 and significant value is 0,024). It means that there is a difference in the value of financial attitude of small businesses accessing formal credit and access to non formal credit. Different mean value of 4,0721 means that the financial attitude of small businesses accessing formal credit is higher than the financial attitude of small businesses accessing non formal credit. Based on the linear regression test that the higher the financial attitude then the higher can access the formal credit. This research is useful for small business actors for business development, for the Government to make financing program policy for the right MSE and financial inclusion, for financial institution to get information about access of formal credit for small business, for academics can be used as reference for further research related to Small Business Entreprise Â financing.